The Role of Sustainable Communication in Hospital Health Services Through Internal Best Practice Sharing Health Talk Activities - Afiat, Muhammad; Rudi Sihaloho; Wulan Furrie Lenggana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Health services in hospitals in serving the community must be maximized, so that knowledge about disease diagnosis is known. As well as preventing premature death or increasing disease among the community. This role of sustainable communication must be carried out by public relations, health experts, namely doctors and other media personnel. To assist the hospital's internal activity program in health education and free basic examinations. So the PROMKES TEAM or Health Promotion Team was formed, consisting of Chief Doctor, Public Relations Officer, Nurse, Nutrition Expert and other medical personnel